Evaluation of effective nucleon-nucleon potential and description of α-cluster type nuclei in restricted dynamics approach - Tambergs, J.; Ruža, J.; Krasta, T.; Castilho Alcarás, J. A. [UNESP]; Katkevičius, O. (World Scientific Publishing, 1997)
The application of the Restricted Dynamics Approach in nuclear theory, based on the approximate solution of many-particle Schrödinger equation, which accounts for all conservation laws in many-nucleon system, is discussed. The Strictly Restricted Dynamics Model is used for the evaluation of binding energies, level schemes, E2 and Ml transition probabilities as well as the electric quadrupole and magnetic dipole momenta of light a-cluster type nuclei in the region 4 ≤ A ≤ 40. The parameters of effective nucleonnucleon interaction potential are evaluated from the ground state binding energies of doubly magic nuclei 4He, 16O and 40Ca.